Musicogenic epilepsy: A Stereo-electroencephalography study. (November 2019) - Pelliccia, Veronica; Villani, Flavio; Gozzo, Francesca; Gnatkovsky, Vadym; Cardinale, Francesco; Tassi, Laura
Abstract: Musicogenic epilepsy is rare focal epilepsy in which seizures are triggered by music. Both spontaneous and reflexes seizures may occur. To date there are limited data about this epilepsy, particularly about its etiopathogenesis. We report the clinical, neurophysiological and imaging data about musicogenic epilepsy in a patient who underwent Stereo-electroencephalography (SEEG) study. A 27 year-old right-handed woman suffering from drug-resistant epilepsy since the age of 17 years, was evaluated for surgery. She had weekly seizures characterized by an unpleasant ascending gastric sensation, tachycardia, occasionally late oro-alimentary automatisms, déjà-vu and vomiting. Only during longer seizures a partial loss of awareness was reported. Interestingly, familiar songs triggered seizures. Rarely, she had spontaneous seizures with the same features. The ictal EEG onset appeared to be right temporal, but there was seizure propagation to suprasylvian areas. Brain MRI was negative. A SEEG implantation was performed to study the right temporo-perisylvian regions. SEEG data clearly indicated the antero-mesial temporal regions as origin of the seizures, without any spread to other close or distant cortical areas. Right temporal antero-mesial resection was performed 24 months ago and the patient is seizure-free since surgery. Neuropathology was uninformative. SEEG data highlighted the hypothesis regarding a temporo-mesial emotional-mnesic network triggered by particular music with an affective component for the patient. The primary auditory cortex and lateral mid-posterior temporal and extratemporal cortices were not involved. Different triggers as mentally singing and hearing the music can induce seizure as well as electrical stimulation in the mesial temporal structures.